2004
DOI: 10.2174/0929867043364351
|View full text |Cite
|
Sign up to set email alerts
|

Torsadogenic Cardiotoxicity of Antipsychotic Drugs: a Structural Feature, Potentially Involved in the Interaction with Cardiac HERG Potassium Channels

Abstract: Many non-cardiovascular drugs of common clinical use cause, as an unwanted accessory property, the prolongation of the cardiac repolarisation process, due to the block of the HERG (Human Ether-a-go-go Related Gene) potassium channel, responsible for the repolarising I(Kr) current. This delayed cardiac repolarisation process can be often unmasked by a prolongation of the QT interval of the ECG. In these conditions, premature action potentials can generate morphologically anomalous after-polarisations, and trigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
36
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 1 publication
1
36
1
1
Order By: Relevance
“…After oral administration, compound 1b was shown to inhibit food intake in rats induced by centrally administered Y5-preferring agonist, NPY, where the minimum effective dose of 1b was 30 mg/kg. 13 Further investigation of leads 1a and 1b was necessary to address issues such as moderate in vivo potency and potent human ether-a-go-go related gene potassium channel (hERG) inhibitory activity 14 in order to identify clinical candidates from this class (Table 1). In this report, compounds 1a and 1b were further optimized by modification of the 2, 4, and 5-positions of the imidazoline substituents, resulting in the identification of a potent and selective derivative, 2a.…”
Section: Introductionmentioning
confidence: 99%
“…After oral administration, compound 1b was shown to inhibit food intake in rats induced by centrally administered Y5-preferring agonist, NPY, where the minimum effective dose of 1b was 30 mg/kg. 13 Further investigation of leads 1a and 1b was necessary to address issues such as moderate in vivo potency and potent human ether-a-go-go related gene potassium channel (hERG) inhibitory activity 14 in order to identify clinical candidates from this class (Table 1). In this report, compounds 1a and 1b were further optimized by modification of the 2, 4, and 5-positions of the imidazoline substituents, resulting in the identification of a potent and selective derivative, 2a.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the binding affinities to the K DR channel of both R-haloperidol and haloperidol were comparable. It is likely the role of carbonyl oxygen was overestimated in the above-mentioned in silico study (Testai et al, 2004).…”
Section: Downloaded Frommentioning
confidence: 89%
“…The oxygen atom in the carbonyl group has been proposed to involve the binding of haloperidol to the central cavity of HERG channels in an in silico study (Testai et al, 2004). Most compounds listed in that study have already been reported as blockers for other potassium channels, including K DR channels.…”
Section: Downloaded Frommentioning
confidence: 96%
See 2 more Smart Citations